Cardiorespiratory fitness and cancer in men with cardiovascular disease: Analysis from the Veterans Exercise Testing Study. (2nd April 2020) - Vainshelboim, Baruch; Chan, Khin; Chen, Zhongming; Myers, Jonathan
Abstract: Background: Cardiovascular disease and cancer share similar risk factors and are the leading causes of death worldwide. This study aimed to assess the association between cardiorespiratory fitness, cancer incidence and cancer mortality in men with cardiovascular disease. Methods: Baseline cardiorespiratory fitness (treadmill exercise test) was assessed in 565 men aged 58.9 ± 17 with documented cardiovascular disease and free from any malignancy. Cox multivariable hazard models, population attributable fraction and exposure impact number were analyzed in model accounting for competing events for cancer outcomes. Results: Mean cardiorespiratory fitness was 7.6 ± 3.4 metabolic equivalents. During a 12.0 ± 7.5 year follow-up, 147 participants developed any type of cancer, 70 died from cancer, and five died from causes other than cancer as competing events. Compared to low cardiorespiratory fitness (<5 metabolic equivalents), moderate (5–10 metabolic equivalents) and high cardiorespiratory fitness (>10 metabolic equivalents) were associated with 50% (0.50, 95% confidence interval (0.27–0.91)) and 68% (0.32 (0.11–0.88)) reduced risks for cancer mortality ( p trend = 0.026), respectively. Survival time was longer among individuals with moderate (20.8 (19.7–22) years) and high (24.9 (23–26.7) years) compared to low cardiorespiratory fitness (17.2 (15.1–19.3) years), p  < 0.001. Population attributable fraction and exposure impact number for cancer mortality were 13% (4.1–17.7) and 10.8 (5.1–56.4), p  = 0.01, respectively. Cardiorespiratory fitness was not associated with cancer incidence. Conclusion: Higher cardiorespiratory fitness was independently associated with lower risk of cancer mortality and extended survival time in men with cardiovascular disease, although it was not associated with cancer incidence. Improving cardiorespiratory fitness through supervised exercise rehabilitation programs could potentially serve as a cost-effective public-health strategy for secondary prevention and survivorship in men with cardiovascular disease.